Thailand’s Approach to Accessing Cashless Society for Baby Boom Generation - Toobunterng, Rosatorn (Journal of Contemporary Social Sciences and Humanities, 2025)
This research applied the qualitative methods in which data were collected through a review of related documents and interviews with key informants. The objectives of this research were to study the process to access a cashless society of the baby boom generation in Thailand, (2) the factors that affect the access, and (3) the policies for accessing the cashless society. The results showed that the process to access the cashless society of the baby boom generation in Thailand required support from the government, private sector, and people. The government of Thailand must initiate a strategic plan to develop a cashless society then the private sectors and banks will develop their own electronics systems that lead to changes in people’s behavior. Factors of the changes in people’s behavior are 8 factors of the unified theory of acceptance and use of technology (UTAUT2). This study recommends that the infrastructure and electronic payment systems continue to be developed. Cashless society must be supported by the government through various government campaigns along with continuously improved by private sectors for a more user-friendly, especially to baby boom generation. To achieve a cashless society, lawmakers ought to establish and promote policy bipartisanly, and most importantly provide education and clear guideline on the electronic payments process to the baby boom generation. With such social support, all baby boom generations in Thailand regardless of education level, social position, income level can enjoy the privileges of a cashless society, which will lead to a smooth transition to a completely cashless society.